2010
DOI: 10.1093/sleep/33.11.1457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Therapeutic Aspects of Childhood Narcolepsy-Cataplexy: A Retrospective Study of 51 Children

Abstract: this study reports on the clinical features of childhood narcolepsy and documents the safe use of treatments commonly used in adults in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
136
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(153 citation statements)
references
References 34 publications
10
136
3
4
Order By: Relevance
“…That report found no impact of the use of sodium oxybate on the occurrence of subsequent puberty. The authors also reported that sodium oxybate alone, or in association with one other drug, modafinil, was sufficient treatment in half of prepubertal cases of narcolepsy-cataplexy [60]. Other published retrospective series reporting the use of GHB in pediatric narcolepsycataplexy have shown similar efficacy and tolerance [88,89].…”
Section: Narcolepsymentioning
confidence: 91%
See 4 more Smart Citations
“…That report found no impact of the use of sodium oxybate on the occurrence of subsequent puberty. The authors also reported that sodium oxybate alone, or in association with one other drug, modafinil, was sufficient treatment in half of prepubertal cases of narcolepsy-cataplexy [60]. Other published retrospective series reporting the use of GHB in pediatric narcolepsycataplexy have shown similar efficacy and tolerance [88,89].…”
Section: Narcolepsymentioning
confidence: 91%
“…In this way, it has been argued that pediatric narcolepsy with cataplexy often co-occurs with a complex movement disorder at disease onset, a phenomenon that may vanish later in the course of the disease [59]. Pediatric narcolepsy-cataplexy is also associated with excessive weight gain near symptom onset, and may be associated with other sleep disorders, including periodic limb movements and sleep apnea, which may obscure or delay the correct clinical diagnosis [60,61].…”
Section: Narcolepsymentioning
confidence: 99%
See 3 more Smart Citations